INVESTIGASI RASIO PANJANG INLET GUIDE VANE DAN DUCTING DENGAN ANALISA NUMERIK TERHADAP POLA ALIRAN DAN KECEPATAN KELUARAN OUTLET DUCTING - anggara, fajar (Universitas Mercu Buana, 2020)
In this research, air flowing from condenser of cold room has been used to turning turbine through ducting. In term of installation the guide vane in the ducting, air flowing is directed to turbine blade. This investigation using ANSYS FLUENT 17 to determine the dimension ratio of length between guide vane and ducting. By comparing three variations A, B and C that the best ratio is B by producing 9.2-9.4 m/s at the outlet of ducting. This is due to the degree of the guide van B is smaller than A and the distance to increase velocity is longer than guide vane C.